Overweight, Thinness, Body Self-Image and Eating Strategies of 2,121 Italian Teenagers. - Roberta Guarino; Alberto Pellai; Luca Bassoli; Mario Cozzi; Maria Angela Di Sanzo; Daniela Campra; Andrea Guala (The Scientific World Journal)
This study describes the prevalence rate of overweight and thinness in a population of teens living in two different areas of Italy and explores the body self-image perception and unhealthy eating behaviours and strategies to lose weight. A questionnaire was administered to a sample of 2,121 teenage students (1,084 males; 1,037 females). Results showed that teen females and males build and perceive their body images in very different ways. Most of the overall sample perceived their weight as normal, while a relevant 31.6% defined themselves as overweight and another 4.4% as heavily overweight. Analysis based on BMI (calculated through self-referred weight and height) showed that only 9.2% of our sample could be considered overweight and 1,7% obese. Most of female teen students (485 out of 1,037) were trying to lose weight, demonstrating that strategies to lose weight were undertaken also by girls perceiving themsleves as normal in relation to body weight; 46.8% girls were using strategies to lose weight compared with 21.9% boys. These strategies included very problematic behaviours like self-induced vomiting (3.3% F vs. 1.7% M) and dieting pills (2.8% F vs. 1.5% M) undertaken along with more usual thinning strategies like dieting and exercising. Girls were more prone than boys to exercise as a way to lose weight (41% vs. 31.7%). This study showed that there is a deep gap between actual weight and perceived body-image and weight. This study is one of the first of this kind in Italy and calls for primary prevention and health education programs aimed at improving teen body-image as a strategy to reduce the eating disorder epidemics spreading among young people.